The Professional and the Academic World Learning Together in Higher Education - Arandia, Maite; Alonso, Israel; Cabo, Aintzane (Opción, 2016)
This article presents the evaluation of an innovative experience carried out in the Social Education Degree program at the University of the Basque Country (UPV/EHU). The experience consists of a space for collaboration and learning between the academic and professional worlds, which is incorporated into the structure of the degree program that began in the 2011-2012 academic year. Throughout this article, we use an evaluative research methodology to present a theoretical basis related to the changes and challenges in Higher Education at the interna tional level, together with a description of the design of the experience, its development, the results, and some conclusions. Higher education, learning, collaboration, active education,